Oxygen concentration modulates the differentiation of muscle stem cells toward myogenic and adipogenic fates - Redshaw, Zoe; Loughna, Paul T. (Elsevier, 2012)
The physiological oxygen concentration of many tissues is far lower than that in which cells are typically cultured in vitro and this may inadvertently influence the proliferation and differentiation potential of many cell types. Muscle derived stem cells, known as satellite cells are responsible for the maintenance and repair of muscle tissue post-natally and in vivo would be exposed to oxygen concentrations of ∼2–5%. Relatively few studies describe the function of these cells in large animal models and here we investigate the influence oxygen concentration has on modulating porcine muscle derived stem cell fate. We compared cells derived from two metabolically distinct muscles, the diaphragm and the hind limb semi-membranosus (SM) muscle. The two sub-populations responded differently to culture at atmospheric (∼20%) and physiological (∼5%) oxygen concentration. While myogenesis was enhanced in both populations at low oxygen, noticeably diaphragm derived cells exhibited greater myotube formation, than those from SM. The trans-differentiation of cells derived from these two sources was similarly affected, with considerable differences seen in adipogenic and neuronal tendencies. In addition to the effect of oxygen on cell phenotype, the expression of key signalling proteins varied between the two sub-populations during early time-points of induced differentiation, suggesting altered regulation of muscle specific stem cells under these conditions. While differences in muscle stem cell potential requires further investigation, the culture of cells in physiological oxygen concentration appears as fundamental to recreating the micro-environmental niche as routinely used factors such as cytokines, substrata and matrices.